UPAYA MENINGKATKAN PENGETAHUAN SAINS MELALUI PENDEKATAN EKSPLORASI LINGKUNGAN SEKITAR UNTUK ANAK USIA DINI - Ai Ina Marlina; Nia Nuraida; Soni Samsu Rizal (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Science is an activity of experimenting or experimenting through observation to find out something. Experiments are the most exciting door to enter the world of science. By experimenting while playing freely children can explore to strengthen the things that are already known and discover new things. Exploring will provide opportunities for children to understand and take advantage of the roaming in the form of; broader and more tangible information insights, fostering a child's sense of curiosity about something he has just discovered. At TK PGRI Dharma Bakti children's science knowledge about the surrounding environment is less developed. This is due to the lack of experience of children in terms of their real knowledge about the environment. Also because of the lack of interest in children towards Science. This study aims to determine the objective conditions of students' science knowledge before using an environmental exploration approach in Group B of the PGRI Kindergarten Dharma Bakti Lumbung District Ciamis District, to determine the process of learning science by using an environmental exploration approach in the Group B of the PGRI Kindergarten Dharma Bakti Kindergarten, Lumbung District, Ciamis Regency and To increase knowledge of Science through the exploration approach of the surrounding environment in group B TK PGRI Dharma Bakti, Lumbung District, Ciamis Regency. This research was conducted with Classroom Action Research. The subject of the research was kindergarten students PGRI Dharma Bakti group B consisting of 10 children, the data analysis technique used was descriptive percentages and descriptive activities of students. The validity of the data uses an observation sheet. Increased science knowledge of kindergarten students PGRI Dharma Bakti through learning with exploration methods around the environment has been proven by observations on the activeness of students in expressing their scientific knowledge in cycles I, II and III. In the first cycle, the percentage of completeness was 40% on the calculation of 3 BBs, 3 MBs, 2 BSH people and 2 BSB people. cycle II completeness percentage is 58% on the calculation of 2 people BB, 2 people MB, 2 people BSH and 4 people BSB. in cycle III the percentage of completeness was 78% on the calculation of 1 BB, 1 MB, 4 BSH and 4 BSB. Kindergarten children PGRI Dharma Bakti looks easy to mention their science knowledge by learning through exploration methods of the surrounding environment. Based on observations from cycle I, cycle II and cycle III it can be concluded that the method of exploration of the surrounding environment can increase the science knowledge of kindergarten students PGRI Dharma Bakti Lumbung District Ciamis Regency